The pathway to cancer Cachexia: Microrna-regulated networks in muscle wasting based on integrative meta-analysis - Freire, Paula Paccielli [UNESP]; Fernandez, Geysson Javier [UNESP]; Cury, Sarah Santiloni [UNESP]; De Moraes, Diogo [UNESP]; Oliveira, Jakeline Santos [UNESP]; De Oliveira, Grasieli [UNESP]; Dal-Pai-Silva, Maeli [UNESP]; Dos Reis, Patrícia Pintor [UNESP]; Carvalho, Robson Francisco [UNESP] (MDPI, 2019)
Cancer cachexia is a multifactorial syndrome that leads to significant weight loss. Cachexia affects 50%-80% of cancer patients, depending on the tumor type, and is associated with 20%-40% of cancer patient deaths. Besides the efforts to identify molecular mechanisms of skeletal muscle atrophy—a key feature in cancer cachexia—no effective therapy for the syndrome is currently available. MicroRNAs are regulators of gene expression, with therapeutic potential in several muscle wasting disorders. We performed a meta-analysis of previously published gene expression data to reveal new potential microRNA-mRNA networks associated with muscle atrophy in cancer cachexia. We retrieved 52 differentially expressed genes in nine studies of muscle tissue from patients and rodent models of cancer cachexia. Next, we predicted microRNAs targeting these differentially expressed genes. We also include global microRNA expression data surveyed in atrophying skeletal muscles from previous studies as background information. We identified deregulated genes involved in the regulation of apoptosis, muscle hypertrophy, catabolism, and acute phase response. We further predicted new microRNA-mRNA interactions, such as miR-27a/Foxo1, miR-27a/Mef2c, miR-27b/Cxcl12, miR-27b/Mef2c, miR-140/Cxcl12, miR-199a/Cav1, and miR-199a/Junb, which may contribute to muscle wasting in cancer cachexia. Finally, we found drugs targeting MSTN,CXCL12, and CAMK2B, which may be considered for the development of novel therapeutic strategies for cancer cachexia. Our study has broadened the knowledge of microRNA-regulated networks that are likely associated with muscle atrophy in cancer cachexia, pointing to their involvement as potential targets for novel therapeutic strategies.
Keywords: Cancer cachexia; MicroRNAs; Protein-protein interaction networks; Transcriptome